2016
DOI: 10.5812/hepatmon.37973
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B and its Relationship With Oxidative Stress

Abstract: ContextDespite the great breakthroughs we have witnessed in the last 50 years in the prevention, diagnosis, and treatment of hepatitis B, we are still far from eradicating or even curing the disease. Achieving further progress in controlling this disease will not be possible without discovering the exact pathogenesis behind it. One prime suspect in the pathogenesis of various diseases is oxidative stress. This review will exclusively explore hepatitis B in the context of oxidative stress to obtain a more compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 77 publications
1
27
0
Order By: Relevance
“…Taken together, the information underscores extremely important awareness regarding the enhanced predisposition to hepatotoxicity incurred by chronic hepatitis C disease and antituberculosis therapy. In chronic hepatitis B infection, there is also some evidence for the occurrence of oxidative stress (52). As in chronic hepatitis C infection, sometimes the studies regarding antioxidant status have yielded rather conflicting results in patients with chronic hepatitis B infection (49,52).…”
Section: Risk Factors Of Antituberculosis Drug-induced Hepatotoxicitymentioning
confidence: 99%
See 2 more Smart Citations
“…Taken together, the information underscores extremely important awareness regarding the enhanced predisposition to hepatotoxicity incurred by chronic hepatitis C disease and antituberculosis therapy. In chronic hepatitis B infection, there is also some evidence for the occurrence of oxidative stress (52). As in chronic hepatitis C infection, sometimes the studies regarding antioxidant status have yielded rather conflicting results in patients with chronic hepatitis B infection (49,52).…”
Section: Risk Factors Of Antituberculosis Drug-induced Hepatotoxicitymentioning
confidence: 99%
“…In chronic hepatitis B infection, there is also some evidence for the occurrence of oxidative stress (52). As in chronic hepatitis C infection, sometimes the studies regarding antioxidant status have yielded rather conflicting results in patients with chronic hepatitis B infection (49,52). This notwithstanding, great vigilance has to be exercised regarding the impact of an ROS-based pathogenetic mechanism in causing antituberculosis drug-associated hepatotoxicity in patients with chronic hepatitis B infection.…”
Section: Risk Factors Of Antituberculosis Drug-induced Hepatotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…As far as we know, this study is the first that investigates the thiol / disulfide homeostasis balance in CHB patients with respect to HBV DNA levels and healthy controls. Studies exist that reveal oxidant-antioxidant imbalance in CHB patients and relate the oxidant-antioxidant state to the ethiopathogenesis and severity of CHB [22]. Various indicators of oxidative stress have been studied in various clinical forms of hepatitis B.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatitis B virus (HBV) infection is one of the most common infectious disease in humans. Despite the success of prophylactic HBV vaccination program and antiviral therapy in decreasing the prevalence of HBV infection, there are still more than 350 million people who suffered from chronic hepatitis B (CHB) virus infection in the world . Remarkably, it has been reported that approximately 1 million people die annually because of HBV‐related disorders, such as HBV‐associated cancer and end‐stage liver diseases .…”
Section: Introductionmentioning
confidence: 99%